Nusing care guide fot intravenous administration of cytotoxicants. Integrative Review - Bermúdez, Zeidy María Vargas (Horizonte Sanitario, 2025)
Objetive. To perform an integrative literature review to establish a care guide for the preparation, handling, administration, prevention and treatment of complications, excreta management and eventualities of intravenous cytotoxic drugs by the nursing professional. Materials and Methods. The integrative review methodology was used, establishing the research question with the acronym PCC (population, concept and context), which describes: What is the best scientific evidence that supports nursing care to people who receive intravenous cytotoxic treatment? The terms cytostatics, cystostatiques, cytostatics, enfermeria, nursing, enfermagen, infirmiers, intravenous, intravenosa, intravenous, intravenous, cuidados, soins, care were used to search for research. The AND and OR operators were used to search for: ("Antineoplastic Agents"[MeSH] AND "Nursing"[MeSH]) OR ("Antineoplastic Agents"[MeSH] AND "Infusions, Intravenous"[MeSH]) AND "Nursing"[MeSH]. Results. From the evidence synthesis, 17 studies were obtained that support the main nursing care pre trans and post intravenous cytotoxic administration. Conclusions. The review of the scientific literature allowed the design of a care guide for the application of intravenous cytotoxic drugs that contains information based on the best scientific evidence identified and constitutes a tool that favors the performance of the nursing staff for the safety of the user receiving the treatment. Keywords. Care; nursing; cytotoxic; intravenous.